Persepsi Mahasiswa kepada Dosen Tamu dalam Meningkatkan Motivasi Menulis Artikel Ilmiah di Kalangan FDK UINSU - Kustiawan, Winda; Riani, Windy; Nurhayani, Nurhayani (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
Guest lecturers are experts or professionals who are brought to universities or educational institutions to deliver lectures or lectures to students. Their presence is often based on special competence or experience relevant to the lecture topic. The purpose of this study is to analyze the perceptions of students of the Faculty of Da'wah and Communication (FDK) of the State Islamic University of North Sumatra (UINSU) towards guest lecturers in an effort to increase motivation to write scientific articles. The method used is descriptive qualitative research involving FDK UINSU students who have attended lectures with guest lecturers. The data collection technique was through distributing questionnaires with 14 FDK students as respondents. The findings of this study indicate that the presence of guest lecturers is considered able to provide inspiration, new insights, and positive encouragement to students to start writing scientific papers. Students feel more motivated after gaining direct experience from guest lecturers who have strong writing backgrounds and experiences. With a qualitative approach, questionnaires are the main tool in collecting data for this study.